2022
DOI: 10.3171/2021.12.focus21419
|View full text |Cite
|
Sign up to set email alerts
|

Heparin in the treatment of aneurysmal subarachnoid hemorrhage: a systematic review and meta-analysis

Abstract: OBJECTIVE Cerebral vasospasm and the resulting infarction remain the most devastating complications of aneurysmal subarachnoid hemorrhage (aSAH). Limited treatment options are available, with nimodipine as the only approved prophylactic medication. In addition to its anticoagulant properties, heparin also has a pleiotropic and anti-inflammatory effect that could be beneficial in vasospasm. In this study, the authors sought to evaluate the efficacy and safety of heparin in the treatment of aSAH. METHODS The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Several prophylactic treatments for cerebral infarction are currently under research, including but not limited to nimodipine, clazosentan, and heparin. 4 , 5 , 6 The availability of an accurate prognostic model can provide tremendous help in risk stratification before beginning treatment. The currently established predictors for aSAH patients are the HH scale, WFNS scale, and modified Fisher scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prophylactic treatments for cerebral infarction are currently under research, including but not limited to nimodipine, clazosentan, and heparin. 4 , 5 , 6 The availability of an accurate prognostic model can provide tremendous help in risk stratification before beginning treatment. The currently established predictors for aSAH patients are the HH scale, WFNS scale, and modified Fisher scale.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, recent years have seen a surge in research trying to find a suitable prophylactic treatment with several drugs showing good potential, such as nimodipine, clazosentan, and heparin. 4 , 5 , 6 With a possible paradigm shift in the treatment strategy of aSAH, an excellent prognostic model is required to identify high-risk patients that would likely benefit from such a preventative treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[21] One systematic review and meta-analysis exploring the association of RDW with prognosis in aneurysmal subarachnoid hemorrhage patients confirmed that higher RDW was associated with a worse functional outcome, a worse discharge and 3-month functional outcome, and a higher in-hospital and 90-day mortality. [22] In another study carried in 8175 community-dwelling adults 45 years or older and exploring the association between RDW and risk of death, the results showed that RDW was a widely available test and a strong predictor of mortality in the general population of adults 45 years or older. [23] In our study, the univariate analysis results showed that the levels of RDW on the preoperative day, the 1st, 3rd and 7th postoperative days were all associated with the prognosis of aSAH patients, further suggesting that RDW might be a highly advantageous prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…The Heparin cohort was 1.9 times less likely to develop delayed neurological damage and 2.5 times less likely to develop cerebral infarction as demonstrated by multivariate analysis. Finally, the meta-analysis of Lukito et al confirmed that heparin treatment for at least 48 h is associated with reduced occurrence of brain infarction showing at the same time adequate treatment safety [152]. Wurm et al analyzed 120 consecutive patients with aSAH (Hunt-Hess I-III), after aneurysm repair, randomly allocated to either one subcutaneous injection of 20 mg enoxaparin or placebo for 21 days following SAH.…”
Section: Heparin and Sahmentioning
confidence: 99%